晚期非小细胞肺癌免疫治疗超进展的研究进展 (Zhongguo Fei Ai Za Zhi, 2021)
Hyperprogressive disease (HPD) is a novel pattern of progression caused by immune checkpoint inhibitors (ICIs). It is characterized by a dramatic tumor surge and is associated with poor clinical outcomes. Up to now, the definition of HPD is still controversial across various studies. Although it has been indicated that HPD has related to multiple clinicopathological features and genetic alterations, it is lack of biomarker to predict its occurrence, and the potential mechanism remains unknown. This review is to summarize current data on HPD specialized in the field of non-small cell lung cancer. And we expect to provide helpful clinical strategies for oncologists using ICIs.